The intrinsic reddening of the Magellanic Clouds as traced by background galaxies: I. The bar and outskirts of the Small Magellanic Cloud - Bell, Cameron P. M.; Martínez-Delgado, David (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present a method to map the total intrinsic reddening of a foreground extinguishing medium via the analysis of spectral energy distributions (SEDs